Study of Fermentation Kinetics of Palm Sap from Cocos nucifera - Shetty, Premalatha; D’Souza, Avila; Poojari, Sangeetha; Narayana, Jayadurgi; Rajeeva, Priya (International Journal of Applied Sciences and Biotechnology, 2017)
Palm wine plays an important role as an alcoholic beverage in traditional practices. It is important to study the biochemical characteristics and microbiological aspects to understand the fermentation kinetics of palm saps. In the present investigation an elaborate study was carried out to study the fermentation kinetics of coconut palm sap. Total sugar, reducing sugar content and glucose concentration was estimated periodically during fermentation for 16h. Microbial load and invertase assay results were related to the changes in sugar concentration. Initial predominance of lactic acid bacteria was followed by dominance of yeasts. Hydrolysis of non reducing sugar occured at a faster rate between 3-9h of fermentation. During this period, the multiplication of yeasts began and reached its peak at 11h fermentation. Ethanol concentration was around 4.0 and 4.1% at 11h and 13h of fermentation respectively. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 375-381